18F-FDG PET/CT in Hepatosplenic Gamma-Delta T-Cell Lymphoma. (September 2015) - Quak, Elske; Salaun, Véronique; Le Naoures, Cécile; Fruchart, Christophe
<x xml:space="preserve">Abstract</x> Abstract Hepatosplenic T-cell lymphoma (HSTCL) is a rare and often difficult-to-diagnose subtype of lymphoma that can occur in the chronically immunosuppressed patient. We present the typical FDG PET/CT findings of HSTCL in a renal transplant recipient. The whole-body metabolic and morphologic information provided by FDG PET/CT can be of great additional value in establishing this diagnosis, thus allowing for a timely start of treatment.